Parents shine by their presence in school: making visible the absence in the cogenetic theory - Dany BOULANGER (Estudos de Psicologia (Campinas), 2022)
Abstract: In this paper, I propose extending Tateo’s systemic cogenetic approach in relation with the dimensions of absence and invisibility. I illustrate my proposition in relation to the phenomenon of school-family-community interaction. I further develop my own theoretical work on how the interaction between school and family is constructed amidst tensions between presence versus absence, as well as visibility versus invisibility. This enables integrating the following dimensions in the systemic cogenetic approach: first, the process of making absence visible, invisible and present; and second, the process of rendering invisible the very process of constructing absence. I also delve into the constructive aspect of absence. I propose extending the systemic cogenetic approach in relation with the following aspects: (a) active absence (Goethe) as a way to make the invisible visible on the edge of the phenomenon; (b) the role of boundary in making visible the invisible; (c) boundary case (Non-Non-A) as a flexible designation (considering a phenomenon as A or non-A); and (d) circular and intransitive movement rendering visible the whole range of phenomena in irreversible time. I use the analysis of parents’ and teachers’ discourse as illustration of these theoretical propositions.